Advancing carbon quantification: A comparative evaluation of gravimetric and volumetric methods for soil carbon assessment in tropical ecosystems - E. Zamora-Ledezma; M. Macías Pro; E. Jarre Castro; J. Vera Vélez; R. Briones Saltos; J. Vélez Velásquez; R. Loor Dueñas; C. Salas Macias; H. Pacheco Gil (Results in Engineering)
This study evaluates methodologies for measuring soil organic carbon (SOC) and inorganic carbon (SIC) in four tropical dry forest (TDF) subtypes along Ecuador's coast. SOC was assessed using gravimetric and volumetric methods, while SIC was determined gravimetrically. SOCgravS showed the highest mean (114.7 Mg C ha−1) but high variability, while SOCvolFAO provided consistent estimates. Strong correlations were observed between gravimetric methods for both SOC and SIC. SOCvolFAO is recommended for large-scale analyses due to its stability and reliability. Limitations include a reduced sample size and lack of deeper soil layers. These findings underpin carbon monitoring and sustainable land management.